The Effect of Choral Response Students Speaking Ability at MTS Pancasila Bengkulu City - Muryaningsi, Aziza; Hakim, M. Arif Rahman; Putra, Pebri Prandika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study explores how the Choral Response method affects the development of English speaking skills of students at MTs Pancasila in Bengkulu City. Using a numerical method with a quasi-experimental design, the study involved two separate groups: an experimental group taught with the Choral Response method, and a control group taught using a general teaching approach. Information was collected through initial and final evaluations that assessed five specific aspects of speaking proficiency: pronunciation, fluency, grammatical accuracy, word usage, and comprehension. The results showed that both groups of students improved in their speaking skills, but the experimental group showed significantly greater improvement overall. The experimental group's mean score increased from 60.55 to 82.27, while the control group's mean score increased from 58.00 to 75.18. An isolated sample t-test showed a significant difference between the groups (p = 0.017 < 0.05), which proved the positive influence of the Choral Response method on students' speaking skills. In conclusion, the Choral Response technique effectively enhances students’ pronunciation, fluency, and confidence in speaking English. It is therefore recommended as an interactive and participatory teaching strategy for developing speaking skills at the junior high school student.